Effectiveness of the two forms of Drugs and Disinfected Solutions on -Oral Microorganism Adhered to Denture Base Materials - Hayam Nori Awad; Seeran Mohammed Ahmed; Shukriya Hussein Habeeb; Aween Auda Ablahad (University of Mosul, College of Dentistry, 2024)
Aims: Microbial adherence to different denture base materials causes denture stomatitis. This study sought to assess the effectiveness of certain antibacterial, antifungal drugs and disinfected solutions. Materials and methods: the drugs were applied in two forms: gel and mouth rinse against various types of candida and bacterial strains that adhered to the two types of denture base materials the acrylic-chrome cobalt and the heat cure acrylic resin denture base materials. The microbial strains used in this study were isolated, by using two different agar mediums Sabouraud's dextrose agar was used for Cryptococcus neoformans, Candida famata, and Candida albicans while blood agar includes Staphylococcus aureus, Corynebacterium diphtheriae, Pseudomonas aeruginosa, lactobacillus acidophilus, Actinomyces Spp., Enterococcus Spp., Streptococcus spp., and E. coli. The susceptibility of candida and bacterial strains against the three types of drugs was determined using nystatin (Nys) in the form of 100000IU /ml suspension and 15gm ointment, and metronidazole (metro) in the form of 250mg tablet diluted in 100000IU/ml of distilled water and 15g 0.75% gel also the chlorhexidine (CHX) 0.20% in the form of both mouthwash and gel used disk diffusion method. The level of inhibition zones was determined in the median and interquartile range due to the small sample size of strain (n=5). The effectiveness of different drugs was examined in the Kruskal-Wallis test. Nonparametric Comparisons for All Pairs. Results: The study showed remarkable outcomes related to the effectiveness of the two forms of the three different drugs against fungi and the bacterial strains associated with the fungi in our samples. Conclusions: The finding specifies that the gel forms are the most effective.